Comparing Investment and Employment Specialisation Patterns of EU Regions - Claudia Stirböck (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
This study analyses relative sectoral specialisation of EU regions on the basis of investment and employment patterns. Controlling for heteroscedasticity and potential endogeneity in the econometric analysis, we find that relative specialisation in manufacturing sectors is higher in central regions. Relative specialisation in services sectors, instead, is stronger in administrative centres as well as peripheral regions. A higher local level of sectoral economies of scale and of productivity strongly increases relative investments in manufacturing sectors. Lower (higher) regional labour costs attract, in particular, higher relative employment shares in labour-intensive (human capital-intensive) sectors.
Keywords: F2; C30; F15; R12; 330; Regional Specialisation; Sectoral Investments; Sectoral Employment; Cross-Section Time-Series Regressions; Internationale Arbeitsteilung; Regionale Arbeitsteilung; Investition; Sektorale Beschäftigungsstruktur; Schätzung; Deutschland